Peningkatan Efisiensi Produksi dan Konsistensi Mutu UMKM Jamu Liciafy melalui Penerapan Teknologi Tepat Guna: Penelitian - Putri Kartika Sari; Muhammad Saufi; Syahrizal Ramadhani; Didik Rio Pambudi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, particularly in job creation, strengthening the real sector, and reducing economic disparities. The herbal medicine industry is one of the MSME subsectors with high potential as it has evolved from traditional products into high-value economic commodities. However, herbal MSMEs often face challenges such as limited capital, low managerial capacity, minimal marketing innovation, and the use of simple production technology, resulting in inconsistent product quality. This community service program aims to enhance the capacity of Jamu Liciafy MSME through technical and managerial assistance, specifically by introducing appropriate technology in the form of a herbal powder crystallization machine and providing product packaging education. The activities were carried out through preparation, implementation, and evaluation stages using a participatory approach. The results indicate improvements in the partner’s understanding of production workflows, ability to operate the crystallization machine, process efficiency, production capacity, and quality consistency. Additionally, packaging and branding training contributed to strengthening product competitiveness. This program demonstrates that integrating appropriate technology with managerial training can sustainably empower MSMEs and support the development of herbal medicine as a cultural heritage and economic asset of Indonesia.